CRISPR/Cas9-Based therapeutics as a promising strategy for management of Alzheimer’s disease: progress and prospects - Khan, Mohamad Sultan; Qureshi, Nousheen; Khan, Rehan; Son, Young-Ok; Maqbool, Tariq (Frontiers in Cellular Neuroscience, 2025)
CRISPR/Cas9 technology has revolutionized genetic and biomedical research in recent years. It enables editing and modulation of gene function with an unparalleled precision and effectiveness. Among the various applications and prospects of this technology, the opportunities it offers in unraveling the molecular underpinnings of a myriad of central nervous system diseases, including neurodegenerative disorders, psychiatric conditions, and developmental abnormalities, are unprecedented. In this review, we highlight the applications of CRISPR/Cas9-based therapeutics as a promising strategy for management of Alzheimer’s disease and transformative impact of this technology on AD research. Further, we emphasize the role of CRISPR/Cas9 in generating accurate AD models for identification of novel therapeutic targets, besides the role of CRISPR-based therapies aimed at correcting AD-associated mutations and modulating the neurodegenerative processes. Furthermore, various delivery systems are reviewed and potential of the non-viral nanotechnology-based carriers for overcoming the critical limitations of effective delivery systems for CRISPR/Cas9 is discussed. Overall, this review highlights the promise and prospects of CRISPR/Cas9 technology for unraveling the intricate molecular processes underlying the development of AD, discusses its limitations, ethical concerns and several challenges including efficient delivery across the BBB, ensuring specificity, avoiding off-target effects. This article can be helpful in better understanding the applications of CRISPR/Cas9 based therapeutic approaches and the way forward utilizing enormous potential of this technology in targeted, gene-specific treatments that could change the trajectory of this debilitating and incurable illness.